Association of common mental disorders with diabetes mellitus - Evidence from community-based matched case-Control study in North India - Harshal Ramesh Salve; Bhushan Dattatray Kamble; Anand Krishnan; Rajesh Sagar; Lakshmy Ramakrishnan; Shashi Kant; Baridalyne Nongkynrih; Vishnubhatla Sreenivas (Wolters Kluwer Medknow Publications, 2023)
Background: Diabetes mellitus (DM) and depression are major public health problems globally. Evidence of linkage of common mental disorders (CMDs) including depression and anxiety disorders with DM is sparsely reported from community-based settings. Objective: The present study aimed to study the association between CMDs and DM among adult population (>30 years) residing in a rural area of North India. Materials and Methods: A community-based case-control study was conducted in 28 villages of Ballabgarh block of Faridabad district of Haryana. Cases (diabetes) were recruited from the community with at least 1 year of diabetes. Age- and sex-matched two neighborhood controls were selected from the same community. Diabetic status was confirmed using glycated hemoglobin. CMDs such as depression and anxiety disorders were screened using PRIME-MD Hindi version. Conditional logistic regression was used to study the relationship between diabetes and CMDs. Results: Total 211 cases (diabetic) and 273 controls (nondiabetic) were approached for the study, of which 173 cases and 175 controls were analyzed. Cases and controls were comparable with respect to age, sex, and socioeconomic status. CMDs were found more among cases as compared to controls (67.5% vs. 37.5%) (P < 0.001). On conditional logistic regression analysis, CMDs were significantly higher among diabetes cases (adjusted odds ratio - 3.2, 95% confidence interval: 1.9-5.2). Conclusion: Strong evidence of coexistence of CMDs and DM from this population-based study necessitates the need of incorporation of management of CMDs into diabetes control program in India.